Land, labor and toxics:: On the production of banana lands in the southern coast of Ecuador - Galarza Suárez, Lucía (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
Bananas are among the world’s most traded fruit. Yet not everyone benefits equally from the fruit’s production and consumption. This article analyzes the political, social and environmental costs of export monoculture through a historical and ethnographic reconstruction of the production of banana lands in Ecuador’s southern coastal region. This analysis centers around the practices of diverse state, business and popular actors confronted with the expansion of large scale plantations, the loss of tropical biodiversity and the incorporation of rural populations into capitalist relations of production. Drawing attention to the co-constitution of society and nature and the testimonies of those living and working in this region, this article seeks to contribute to a greater understanding of the extractivist logics and practices promoted by the territorialization of both state and capital interests in rural worlds throughout the diverse historical stages of their expansion.